2021
DOI: 10.1021/accountsmr.1c00233
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal Swimming Nanorobots

Abstract: Conspectus Room temperature liquid metal gallium-based materials have received tremendous attention owing to their potential promises in various aspects including bioengineering and smart medicine, flexible circuits and electronic skins, transformable activators and triboelectric nanogenerators, etc. Particularly, the usage of gallium-based liquid metals to construct humanoid robots to accomplish diverse dangerous missions leads to the considerable focus on the development of gallium-based flexible robots. Unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…[21] LM micro-/nanomotors with well-designed surface chemical reactions with the surrounding environment and architectures for effective propulsion in biological fluids and performance of the desired functions in specific locations have also been explored for targeted therapy. [24,[64][65][66][67][68] For instance, enzymes with high biocompatibility have been explored for targeting drug delivery to improve therapeutic effects. Enzyme-powered targeted transportation of LM was developed by modifying enzymes on the LM surface.…”
Section: Enhanced Targeting Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[21] LM micro-/nanomotors with well-designed surface chemical reactions with the surrounding environment and architectures for effective propulsion in biological fluids and performance of the desired functions in specific locations have also been explored for targeted therapy. [24,[64][65][66][67][68] For instance, enzymes with high biocompatibility have been explored for targeting drug delivery to improve therapeutic effects. Enzyme-powered targeted transportation of LM was developed by modifying enzymes on the LM surface.…”
Section: Enhanced Targeting Abilitymentioning
confidence: 99%
“…Moreover, LMs applied for target treatment can also be achieved by converting chemical energy into mechanical forces through heterogeneous microstructure construction. [65,66,68] A Janus microstructure motor designed by asymmetrically coating Ga on zinc (Zn) microparticles showed self-propulsion behavior in simulated gastroenteric acid. This motion of Ga/Zn micromotors propelled by hydrogen bubbles generated by the zinc-acid reaction was improved by Ga-Zn galvanic effects, which can be applied for targeting antimicrobial chemotherapy (Figure 5e).…”
Section: Enhanced Targeting Abilitymentioning
confidence: 99%
“…[3,42] These properties and the ability to tune the physical properties, i.e., surface/interfacial tension, thermal conductivity, and rheological properties (viz., viscosity) as well as the ability to actuate and deform the liquid metals via ample methods and phenomena, such as fuel-propelled, Marangoni effect, magnetic field, electrical field, light, and ultrasound field, render them intriguing candidates for various applications, including high-precision manipulation, flexible electronics, soft robotics, and drug delivery systems. [2,[49][50][51][52][53][54][55][56] For example, Xu et al [53] reported a kind of magnetic liquid droplet robot that can move due to a magnetic gradient field and this robot is able to perform cargo transfer and vessel cleaning. Sheng et al [57] showed that the liquid metal is capable of performing diverse transformations between different morphologies by changing the location of the electrodes and the applied voltages.…”
Section: Introductionmentioning
confidence: 99%
“…However, the forces exerted by IFT-induced movement are rather small. Therefore, other strategies for liquid metal soft robot actuation have been developed, which are based on internal fuels, ultrasound, and magnetic field actuation [ 18 , 19 , 20 , 21 , 22 ]. Although many LM droplet-enabled soft robotic systems have been reported and applied in copious areas, such as microfluidic pumping, cargo transportation, and drug delivery, they are still limited by the fact that they have fewer shape-shifting patterns and small actuation strains.…”
Section: Introductionmentioning
confidence: 99%